An Assessment of Sustainable Development in the South Central Coast of Vietnam during the Period from 2010 to 2016 - Le, Thi Ly (H. : ĐHQGHN, 2019)
In the context of global change, the rapidly increase of socio-economic development can trigger the negative impacts on coastal resources, environment and ecosystems, causing the deterioration of the system sustainability. Vietnam is one of the most vulnerable countries by climate change. Of which, the South Central Coast (SCC) is a highly vulnerable area to climate extreme events and sea level rise. This research aimed to build a theoretical framework for evaluating the level of sustainable development in the SCC. By using Delphi method, Interpolation method and Evaluation method, the research proposed a set of indicators, which consists of 32 indicators of the four dimensions (Economic; Social; Environmental; Infrastructure and Governance) in order to evaluate the sustainable development index (SDI) of the SCC provinces. Results show that the SDI had an increased tendency from 2010 to 2016. In general, Da Nang is the capital of the region and the SDI was highest which increased from 0.38 in 2010 to 0.61 in 2016 through the development of economic, infrastructure and urban governance dimensions. In contrast, during the survey, Binh Dinh and Phu Yen’s SDI were still lower than other provinces. Results suggested that it is necessary to enhance the policy and planning to implement the sustainable development goals together with the economy, society, environment and infrastructure development. The sustainable development indicators can potentially contribute to apply to monitor the sustainable development in other coastal regions in Vietnam.